Konut site yönetimlerinde yönetim ve muhasebe sistemi, maliyetlerin oluşması ve bir örnek uygulama - Torba, Naci (My University, 2005)
The family and family members, the first and smallest core of the society, deserve for a an independent residence to live during their life. The production process to meet such a need for residence is a complex one and needed many people and institutions to be involved. This complex structure of production is a nationwide process. Residential areas (site houses) are joint - life areas. In order to provide a reliable, peaceful and high quality living to the owners of houses in a residential area, owners of houses forms a management body, which is actually a non-commercial business unit? During the preparation of this study, we separately studied the accounting systems, enrolments and booking applications. We have visited Basin Konut Sitesi and Başakşehir Siteleri managements to see applications on site. We searched accounting books, enrolment books, financial reports and documentation applications as well as face to face meetings with managers, financial controllers and stuff. We noted problems about the management systems and legal problems and observed wrong or insufficient applications. We studied the history and progress of construction and residential blocks, the nature of them and legal status and tried to make statements about the benefits of system as well as positioned the law. The second chapter designed to study the management structure, board of directors, board of auditors, and status of tenants. The third chapter of the thesis studies the costs of residential block managements and how these costs are distributed among the residents. We studied the management and accounting system of Basaksehir Etap 2 residential blocks. We also explained the management system of the Site as a case study. Chapter 5th tries to provide conclusions of study and we submitted documents and attachments in the last chapter. As a result, the management, auditing and especially accounting systems and legal codes for the residential blocks are not sufficient. For that reason, managing of residential blocks are run under the code of apartment possession. Considering the significant number of residential blocks in Turkey, there should be a special code to regulate the accounting and financial systems of residential blocks. The lack of such a regulation causes auditing problems as well as probes. There should be a standardized accounting system to be prepared by Turkiye Accounting Standarts Committee according to Standardised Accounting System . All accounting systems of residential blocks should be constructed according to that proposed system.

Toplumun en küçük yaşama birimi olan aileler ve bu ailelerin fertleri, içerisinde sürekli olarak yaşayabilecekleri bağımsız birer konuta sahip olmak isterler. Sözü edilen konut ihtiyaçlarının karşılanması için yapılması gereken üretim, birçok kişi ve örgütün katıldığı, karmaşık bazı süreçleri içeren bir bütün olarak karşımıza çıkar. Bu bütün ulusal düzeyde konut üretim ihtiyacını oluşturur. Site bir ortak yaşam alanıdır. Sitede yaşayan kat maliklerine huzurlu, güvenli ve düzeyli bir yaşam için, kat malikleri tarafından oluşturulan ve site adı verilen işletme tarafından hizmet verilir. Tezin hazırlık aşamasında; çeşitli site yönetimlerinin muhasebe organizasyonları ile kayıt sistem ve uygulamaları, başta Basın Konut Sitesi ve Başakşehir Siteleri olmak üzere çeşitli site yönetimleri ayrı ayrı yerinde incelenmiştir. İlgili yönetici, denetçi ve personel ile bizzat yapılan görüşmelere paralel olarak, muhasebe defter kayıtları ve belge düzeni, mali tablolar incelenmiş; ilgililerin sistem ile ilgili sorunları dinlenmiş, gözlenen yanlış yada eksik uygulamalar ile ilgili açıklamaları derlenmiştir. Tezin birinci bölümünde; inşaat ve toplu konutların tarihçesi, niteliği, gelişimi ve hukuki yapısı incelenmiş, faydaları ve sitelerin hukuk karşısındaki durumları açıklanmaya çalışılmıştır. Tezin ikinci bölümünde; site yönetim organizasyonu, yönetim kurulu, denetim kurulu ve kiracılarla ilgili çeşitli sorunların çözümleri açıklanmıştır. Tezin üçüncü bölümünde; sitelerde oluşan maliyetler incelenmiş ve bu oluşan maliyetlerin üyelere dağıtımı açıklanmıştır. Tezin dördüncü bölümünde; Başakşehir 2. etap sitesi, yönetimi ve muhasebe sistemleri ile birlikte incelenmiş ve örnek uygulama ile Site Yönetim Sistemi açıklanmıştır. Tezin beşinci bölümünde; tez ile ilgili sonuçlar ortaya konulmaya çalışılmış ve altıncı bölümünde de konuyla ilgili dökümanlar ek olarak sunulmuştur. Sonuç olarak; konut sitelerinin yönetim, denetim ve özellikle muhasebe sistemi konusunda gerekli ve yeterli düzenleme yoktur. Bu sebeple yönetim ve denetim konularında Kat Mülkiyeti Kanununun ışığında çalışır. Ülkemizde konut sitelerinin oldukça yaygın olduğu ve yayılmaya devam ettiği bir dönemde özellikle muhasebe ve mali konularda site yönetimlerine özel bir düzenlemeye gidilmelidir. Zira bu serbestlik, denetim güçlüklerine ve ciddi suiistimallere neden olmaktadır. Konuyla ilgili olarak Tek Düzen Muhasebe Sistemi bağlamında Türkiye Muhasebe Standartları Kurulu tarafından konut siteleri için muhasebe standardı oluşturulmalı ve konut sitelerinde muhasebe düzeni bu standartlara göre yeniden yapılandırılmalıdır.
Keywords: Muhasebe; Site Yönetimi; Yönetim ve yardımcı hizmetler